Language and cognitive interference: How using complex scientific language limits cognitive performance. Issue 4 (13th March 2019) - Brown, Bryan A.; Donovan, Brian; Wild, Andrew
Abstract: Language is seen as a gatekeeper to science learning for many students. This randomized experimental study explores how learning science through complex language reduces working memory capacity. A sample of 64 students aged 14–17 years was randomly assigned to two conditions. The control group watched an instructional video about the water cycle taught using complex scientific language. The experimental group watched the same video with simple scientific language replacing the more complex alternatives. After instruction, students were asked to complete a Stroop test and a Flanker test measuring cognitive capacity. There were no significant differences across the treatment groups in students' ability to answer questions correctly. However, the results revealed statistically significant differences in the rate of students' responses to complicated items. When students needed to answer questions with increased cognitive difficulty, the experimental group ( everyday language condition ) answered significantly faster than the control group. These results suggest that complex scientific language is a potential inhibitor of cognitive capacity for students.